2021
DOI: 10.1139/tcsme-2019-0294
|View full text |Cite
|
Sign up to set email alerts
|

Wear behavior of B4C reinforced Al 6063 matrix composite electrodes fabricated by stir casting method

Abstract: The aim of the study is to predict the surface topological characteristics of Al-B4C composite electrodes and the OHNS Die steel in the Electrical Discharge Machining (EDM) Process. The surface characteristics of Composite electrodes are evaluated by using Scanning Electron Microscopy (SEM) and EDAX Analytical Method. Surface roughness and hardness of the OHNS die steel was measured by the Stylus probe and Brinnel hardness. The composite electrodes prepared by the Aluminium 6063 and B4C materials. Both element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The amount of beryl particles added had no positive effect on the weight loss caused by sliding wear. When contrasted with the basic alloy, the specific wear rate dropped 8.9% [8]. The impact of microwave sintering on the production of aluminium beryl MMCs and published their findings.…”
Section: Introductionmentioning
confidence: 96%
“…The amount of beryl particles added had no positive effect on the weight loss caused by sliding wear. When contrasted with the basic alloy, the specific wear rate dropped 8.9% [8]. The impact of microwave sintering on the production of aluminium beryl MMCs and published their findings.…”
Section: Introductionmentioning
confidence: 96%
“…Kumar et al [15] fabricated graphene (5% and 10 wt%)-reinforced AA6061 MMC for improved mechanical and wear behavior. Hussein Alrobei [16] also analyzed the reinforcement of AA6061 with SiC and B 4 C, and Sundaram et al [17] added only B 4 C to AA6063 for the fabrication of MMC through stir casting and reported results of improvements in wear resistance and hardness. Different weight percentages of Ni (i.e., 1%, 5%, 10%, and 15%) were also applied by Nath and Arul [18] on the well-known high-strength aluminum aerospace alloy, AA7075, for an Al 3 Ni intermetallic phase compound because of the low solubility of Ni in aluminum.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was discovered that a drop in efficacy had occurred for only weakly linked micro-particles [9]. Research on porosity nucleation in metal composites has shown that reinforcement coatings, such as Cu on SiC, decrease the contact angle and enhance the wettability of the interface.…”
Section: Introductionmentioning
confidence: 99%